2022
DOI: 10.1212/wnl.0000000000013087
|View full text |Cite
|
Sign up to set email alerts
|

Glial Fibrillary Acidic Protein Autoimmunity

Abstract: Objectives:To report the clinical, biological, imaging features, and the clinical course of a French cohort of patients with glial fibrillar acidic protein (GFAP) autoantibodies.Methods:We retrospectively included all patients tested positive for GFAP antibodies in the cerebrospinal fluid, by immunohistochemistry and confirmed by cell-based assay using cells expressing human GFAPα, since 2017, from two French referral centers.Results:We identified 46 patients with GFAP antibodies. Median age at onset was 43 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 39 publications
(70 reference statements)
8
84
0
Order By: Relevance
“… 3 Impairment of astrocytes might be mediated by T cells and other inflammatory components of the immune system. 3 , 4 , 29 Given that both AQP4 and GFAP are pivotal in astrocytes, we might hypothesize that impairment of astrocytes in the AP or related neural network could cause clinical symptoms of APS in autoimmune GFAP astrocytopathy. Further pathologic studies of the AP and development of animal models are needed to elucidate the pathogenesis of astrocyte dysfunction and its association with APS in GFAP-IgG–related autoimmune astrocytopathy.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Impairment of astrocytes might be mediated by T cells and other inflammatory components of the immune system. 3 , 4 , 29 Given that both AQP4 and GFAP are pivotal in astrocytes, we might hypothesize that impairment of astrocytes in the AP or related neural network could cause clinical symptoms of APS in autoimmune GFAP astrocytopathy. Further pathologic studies of the AP and development of animal models are needed to elucidate the pathogenesis of astrocyte dysfunction and its association with APS in GFAP-IgG–related autoimmune astrocytopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical spectrum of GFAP autoantibodies to date comprises patients with meningoencephalitis, headache, visual problems, often febrile temperature, abnormal movements (9), or hyponatremia (10). A recent study confirmed that the main clinical presentation associated with GFAP autoantibodies are subacute meningoencephalitis with dysfunction in cerebellar pathways (11). Myocloni and bulbar syndrome (12) as well as blindness (13) and vision loss (14) appear to be less frequent manifestations of GFAPautoantibody disease.…”
Section: Introductionmentioning
confidence: 99%
“…Myelitis has been demonstrated in 30% of patients ( 16 ), with one study finding myelitis as the presenting symptom in 10.5% ( 14 ). Isolated myelitis is rare and in onset study identified in 5% ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Patients may have a monophasic, relapsing, or progressive course despite treatment ( 14 ). Other presenting symptoms outside of myelitis may include rhomboencephalitis, cerebellar dysfunction, swallowing difficulties, cognitive difficulties , seizures, parkinsonism, myoclonus, dysautonomia, optic disc edema, optic neuritis, uveitis, and cranial nerve palsies affecting vision ( 14 , 16 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation